Development of dental clinic cooperativity predictor instrument for children with autism spectrum disorder - Octavia, Alfini; Saskianti, Tania; Mohd Dom, Tuti Ningseh; Dewanto, Iwan; Azzahra, Syaina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: A survey to identify factors affecting the cooperation of children with autism spectrum disorder (ASD) in Indonesia is crucial for enhancing this group’s dental care, oral health, and overall quality of life. However, limited culturally relevant instruments hinder such research. Purpose: This study aims to determine the essential domain needed to design a questionnaire instrument that can predict the cooperativity of children with ASD during dental procedures. Methods: Based on the literature and existing questionnaires, the newly developed questionnaire underwent forward–back translation, before being thoroughly reviewed by an expert committee. The response format, content, and question clarity were evaluated. A cross-sectional study with 30 parents of children with ASD was randomly conducted to test the questionnaire. The validity of each question was measured by the Pearson product-moment correlation coefficient, while its reliability was assessed by Cronbach’s alpha. Results: Each question within the domain showed varying degrees of validity: reading ability (r = 0.658), daily communication (r = 0.541), involvement in social activity (r = 0.360), daily self-care ability (r = 0.506), emotional status (r = 0.426), sensory responsiveness (r = 0.615), language comprehension (r = 0.362), and permission to be touched on the head at a barbershop (r = 0.458). The questions were found to be reliable (Cronbach’s alpha, r = 0.645 > 0.306). Conclusion: As prediction tools for assessing the cooperativity of children with ASD during dental procedures, the questionnaire should include the following items: communication and reading abilities, daily self-care, social activity, emotional status, sensory responsiveness and permission to be touched on the head at a barbershop.